KNOWLEDGE SHARING IN JORDAN PHARMACEUTICAL INDUSTRIES - Asmahan M. Altaher (European Scientific Journal, ESJ, 2013)
This paper describes a kind of research in the field of information systems, more specifically, knowledge sharing system. This paper seeks to explore; how knowledge sharing system in Jordan pharmaceutical industries helped in create new products. The researcher built and tests a model of the knowledge sharing techniques that support create new knowledge internal firms. In order to know the impact of these techniques within the Jordan pharmaceutical firms, in an attempt to know its effect on increasing continues sharing and learning internal the pharmaceutical firms. The results of the survey on 224 respondents in several pharmaceutical firms in Jordan revealed that Companies should focus on continued improvement of the techniques that they use for sharing knowledge. The researcher recommends that the employees must have the chance to apply what they have learnt through the training or double loop learning. Finally the firms should maintenance of current knowledge resources, because they are considered one of the ways to innovation.